Pengaruh Penggunaan Handphone Terhadap Minat Baca Siswa Kelas VII di MTs. Muhammadiyah Wuring - Sumardhiyati R. Syarif; Danar Aswim; Abdullah Muis Kasim (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This study aims to determine how the influence of mobile phone use on students' reading interest and to determine the supporting and inhibiting factors of student reading interest on the use of grade VII students' mobile phones at MTs. Muhammadiyah Wuring. The method used in this study is using a descriptive qualitative approach. The informants in this study were the Principal (represented by Kaur kesiswaan), Homeroom Teacher, and several grade VII students at MTs. Muhammadiyah Wuring school. The results found that the effect of mobile phone use on students' reading interest was high. due to misuse of mobile phones by students.